ChemInform Abstract: Gold(I)‐catalyzed Formation of Bridged and Fused Carbocycles. Issue 44 (14th October 2013) - Barabe, Francis; Levesque, Patrick; Sow, Boubacar; Bellavance, Gabriel; Betournay, Genevieve; Barriault, Louis
Abstract Review: 52 refs.